Human neuroblastoma cells with acquired resistance to the p53 activator RITA retain functional p53 and sensitivity to other p53 activating agents - Michaelis, Martin; Deimling, Andreas von (Cell death & disease, 2012)
Adaptation of wild-type p53 expressing UKF-NB-3 cancer cells to the murine double minute 2 inhibitor nutlin-3 causes de novo p53 mutations at high frequency (13/20) and multi-drug resistance. Here, we show that the same cells respond very differently when adapted to RITA, a drug that, like nutlin-3, also disrupts the p53/Mdm2 interaction. All of the 11 UKF-NB-3 sub-lines adapted to RITA that we established retained functional wild-type p53 although RITA induced a substantial p53 response. Moreover, all RITA-adapted cell lines remained sensitive to nutlin-3, whereas only five out of 10 nutlin-3-adapted cell lines retained their sensitivity to RITA. In addition, repeated adaptation of the RITA-adapted sub-line UKF-NB-3rRITA10 μM to nutlin-3 resulted in p53 mutations. The RITA-adapted UKF-NB-3 sub-lines displayed no or less pronounced resistance to vincristine, cisplatin, and irradiation than nutlin-3-adapted UKF-NB-3 sub-lines. Furthermore, adaptation to RITA was associated with fewer changes at the expression level of antiapoptotic factors than observed with adaptation to nutlin-3. Transcriptomic analyses indicated the RITA-adapted sub-lines to be more similar at the gene expression level to the parental UKF-NB-3 cells than nutlin-3-adapted UKF-NB-3 sub-lines, which correlates with the observed chemotherapy and irradiation sensitivity phenotypes. In conclusion, RITA-adapted cells retain functional p53, remain sensitive to nutlin-3, and display a less pronounced resistance phenotype than nutlin-3-adapted cells.